Polyethylene on Cement Spacers: An Economic Approach to an Effective Infection Eradication in a Two-Stage Knee Revision Articulating Spacers - Lu, Junren; Han, Jing; Zhang, Chi; Yao, Zhenjun; Yang, Yi (The Journal of Knee Surgery, 2018)
Although two-stage revision surgery is generally considered as the gold standard treatment for periprosthetic joint infection (PJI) after total knee arthroplasty, the procedure is limited by the costs of commercially preformed spacers used for treatment. In this work, we aim to report a modified approach by which the cost of the spacer could be significantly reduced without compromising eradication of infection. Between 2010 and 2016, we performed a total of 11 two-stage revision arthroplasties using a surgically handmade spacer with a new polyethylene insert. Patients were aged 59 to 80 years old (mean 69.9 years), with a range of motion (ROM) between 20° and 65° on the affected knee (mean 46.4°) before the first-stage revision surgery. During the perioperative and postoperative period, functional and clinical evaluation of the patients were performed, including the determination of their articular ROM, Knee Society Knee Scores (KSKS), and Knee Society Function Scores (KSFS). All patients were followed up for an average of 2 years, ranging from 1 to 4 years. After the second-stage revision surgery, the mean ROM was increased by 46.8° (46.4°–93.2°) after the second-stage revision. KSKS and KSFS scores were recorded to increase by an average of 44.5° (range 40.4°–84.9°) and 46.9° (range 38.5°–85.4°), respectively. All 11 patients underwent a successful two-stage revision surgery, and no evidence of postsurgical infection was found during patient follow-up examination. Our results show that this personalized handmade antibiotic-loaded articulating spacer is cost-effective and efficacious.
Keywords: periprosthetic joint infection; total knee arthroplasty; infection; articulating spacer; two-stage revision